Evidence of Global Warming from Zakho Precipitation Data - Azooz, Aasim A.; Bahraw, Sonya Z. I. (Science Journal of University of Zakho, 2018)
Analysis of available precipitations data for Zakho area supports the argument that global warming has affected this region. Results shows that monthly and yearly rain fall have been decreasing systematically since the thirties of the last century until now. Based on linear correlation model, some future estimations of the reduction in precipitation as related to the global atmospheric carbon dioxide concentrations are made.